Fin de Sicle/Fin du Globe
XI, 248 p.
Keywords: The internationally distinguished scholars who have contributed to this timely book were asked to take part in a collaborative act of demystification: a reconsideration of the eschatological ideas of the last fin de sicle, the 1890s, in the light of the critical thought of the 1990s. Their essays draw upon a range of approaches, and are broadly interdisciplinary. All are characterised by the realisation that, with a century's hindsight, the late 1800s should be seen not so much as a period of decadence as of discovery and growth.